Potret Masyarakat Moi Di Tanah Papua (Tinjauan Sosial Budaya Terhadap Potret Masyarakat Moi di Tanah Papua) - Leuwol, Natasya Virginia; Boekorsyom , Claudia D.; Rumbekwan , Monalisa I. E.; Tousalwa , Marsya; Titirloloby , Ariel S.; Manutmasa , Magdalena F. (CV. ITTC INDONESIA, 2024)
Moi society is an Indigenous of Papua lives mainly in Sorong and Raja Ampat. Moi ethnic that lives in Raya Ampat and Sorong region now are consist of eight sub ethnic that are Moi Legin, Moi Abun, Moi Karon, Moi Klabra, Moi Moraid, Moi Segin, dan Moi Maya, which spread out into certain other regions. Traditionally, Moi society has inherited rich and complex cultural legacy that are protected and conserved those existed tradition in their daily life with a very strong communal sense. Main focus of this research is the traditional aspects that still implemented such as social system, family structure, cultural values, traditional rituals, local language dan interaction with the environment and community.